2021
DOI: 10.1556/2006.2021.00070
|View full text |Cite
|
Sign up to set email alerts
|

Hands-off: Feasibility and preliminary results of a two-armed randomized controlled trial of a web-based self-help tool to reduce problematic pornography use

Abstract: Background and Aims Despite problematic pornography use (PPU) being prevalent, no previous study has examined the effectiveness of evidence-based interventions for PPU, using rigorous methods. Using a two-armed randomized controlled trial study design, we examined the feasibility and initial effectiveness of a six-week online PPU intervention. Methods We recruited 264 participants (3.8% women, M age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 72 publications
0
51
2
2
Order By: Relevance
“…There were 2 studies for internet reduction that reported an average of 5.5 hours of screen time per day [ 52 , 53 ]. The average frequency of engagement was 6 times per week [ 20 , 45 , 46 ], with 2 studies involving gamblers reporting a frequency of 13 times a month for internet gambling [ 54 ] and another study reporting 62 sessions a month for online poker [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were 2 studies for internet reduction that reported an average of 5.5 hours of screen time per day [ 52 , 53 ]. The average frequency of engagement was 6 times per week [ 20 , 45 , 46 ], with 2 studies involving gamblers reporting a frequency of 13 times a month for internet gambling [ 54 ] and another study reporting 62 sessions a month for online poker [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies (ten arms) reported the delivery of cognitive restructuring [ 45 , 51 , 54 , 55 ], cognitive bias modification (CBM) [ 47 , 50 ], exposure therapy [ 49 ], or mindfulness [ 53 ]. Cognitive restructuring prompted participants to identify, challenge, and replace automatic negative thoughts associated with gaming, gambling, pornography, and nonspecified internet use.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pornography use disorder. For pornography use disorder, Bőthe, Baumgartner, Schaub, Demetrovics, and Orosz (2021) assessed one internet-based intervention, which consisted of CBT in combination with MI. The intervention provided participants with modules targeting the identification of risk situations, behavioral activation, identification of triggers, and challenging automatic negative thoughts.…”
Section: Study Characteristicsmentioning
confidence: 99%